Download presentation
Presentation is loading. Please wait.
Published byMichael Wheeler Modified over 9 years ago
1
Notes - Solving Quadratic Equations in Factored Form If ab = 0, then a = 0 or b = 0 If the product of two factors is zero, then at least one of the factors must be zero. 3 * 0 = 00 * 3 = 00 * 0 = 0
2
Notes - Solving Quadratic Equations in Factored Form (x + 3)(x + 2) = 0
3
Ex. 1: Solve the equation (x-2)(x+3) = 0 STEP 1: Set each factor equal to zero. x-2= 0 and x+3 = 0 STEP 2: Solve for x. x-2= 0 x = 2 x+3 = 0 x=-3 STEP 3: Check your answers. (x-2)(x+3) = 0 (2-2)(2+3) = 0 (0)(5) = 0 0 = 0 (x-2)(x+3) = 0 (-3-2)(-3+3) = 0 (-5)(0) = 0 0 = 0
4
Solve 1) x 2 + 5x + 6 = 0 2) x 2 – 2x – 8 = 0 3) x 2 + 7x + 6 = 0 4) 3x(2x + 5) = 0
5
Answers 1) x = -3, -2 2) x = -2, 4 3) x = -1, -6 4) x = 0, -5/2
6
$25,000 Pyramid
7
(x+1)(x+3)x = -5, -3x = -6, -5(x+4)(x+6) x = 6, x-5 (x-8)(x+5) x = 18, -3 x =20, -10 (x-12)(x+4) x=15, -6
8
$25,000 Pyramid (x+1)(x+5)X=-9, -2(x+4)(x+8)x= -7, -9 (x-5)(x+4) (x-6)(x+3) (x-13)(x+3) (x-10)(x+10) X=11, x=-6 (x-14y)(x+5y)
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.